Entropy solutions for nonlinear elliptic anisotropic problem with Robin boundary condition - Stanislas Ouaro; Bernard Kaka Bonzi; Frederic D. Zongo (Le Matematiche, 2013)
We study a Robin boundary value problem of nonlinear elliptic anisotropic type. We prove the existence and uniqueness of entropy solutions for $L^{1}$-data, via the existence and uniqueness of weak solution.